Seleção fenotípica e identificação de snps em regiões genômicas ligados a resistência à ferrugem em Eucalyptus grandis - Pereira, Gleice Viviane Nunes [UNESP] (2015)
Widely disseminated in Brazil, causing huge losses in nurseries and commercial plantations, eucalyptus rust, incited by Puccinia psidii, is currently one of the main diseases of eucalyptus plantation. The search for resistant progenies is facilitated when information regarding the genetic control of resistance and selection trategies as an assisted selection by molecular markers are available. This study objective was to estimate genetic parameters, assess the genetic gain by selection for partial resistance to rust caused by P. psidii in Eucalyptus grandis of F1 progenies, as well as identification of SNPs (single nucleotide polymorphisms) in genes chitinase and β-1,3-glucanase related to resistance. This study was divided into two chapters. The first chapter was conducted in the city of Itararé-SP, which were installed two experiments with 88 F1 progenies of Eucalyptus grandis. The experimental design utilized was a randomized complete block design with four replications and five plants per plot, totaling 1760 plants per experimental field. At 30 days after planting was carried out the first assessment regarding the occurrence of rust, by the rating scale. Four monthly evaluations were carried out from September to December ...